2016
DOI: 10.1097/anc.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Infants With Technology Dependence

Abstract: Methods to prevent readmission and ensure successful discharge from hospital to home is indicated. Standardization of a discharge process of infants of technology dependence combining medical team, family, outpatient coordinators, and primary care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Analysis of total number of admissions in our cohort was 127, meaning an average of 3 hospital admissions in 5 years per child, similar to a previous study with a 3.8% admission rate after tracheostomy during a 5-year period [ 4 ]. Several other studies have documented increased hospital readmissions of technology-dependent infants during the first year of life [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Analysis of total number of admissions in our cohort was 127, meaning an average of 3 hospital admissions in 5 years per child, similar to a previous study with a 3.8% admission rate after tracheostomy during a 5-year period [ 4 ]. Several other studies have documented increased hospital readmissions of technology-dependent infants during the first year of life [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 83%
“…Current advancements in obstetrical and neonatal care have shown a marked increase in survival rate for infants admitted to the NICU over the past few decades [ 2 ]. At the same time, the survival of infants requiring a complex medical care has led to a growing population of technology-dependent infants with significant medical needs [ 3 , 4 ]. Technology-dependent infants require a higher level of care, intensive parental teaching and discharge coordination from a multidisciplinary team both in the hospital and at home [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There could be some reasons for that (1) the parents had expected to have a full-term infant, so they did not learn about potential neonatal diseases, such as pneumonia, jaundice, respiratory insufficiency, and gastrointestinal diseases; and (2) the no-visitation policy limited the communication between parents and HCPs, so the parents could not enter the NICU without an appointment and thus had few opportunities to talk with HCPs. As the previous study suggested, the parents' perspectives and attitudes towards their infant's condition were related to the infant's after-discharge conditions and readmission rates (Bowles et al, 2016). Therefore, helping the parents understand the preterm infant's disease information and caring knowledge might smoothen the discharge preparation process.…”
Section: Discussionmentioning
confidence: 90%
“…Sharing the updates about the infant's health conditions and encouraging the parents to engage in decision-making through more frequent and effective communication with HCPs is a flexible strategy to promote parents' engagement (Bracht, OʼLeary, Lee, & OʼBrien, 2013;Galarza-Winton et al, 2013;Gupta et al, 2019). In the future, if the no-visitation policy could be changed, we can create more opportunities for parents to stay with their infant at bedside to facilitate the parent-infant bonding and to learn about infant non-body clues, facial expressions and regular or irregular symptoms (Bowles et al, 2016;Heinemann, Hellström-Westas, & Hedberg Nyqvist, 2013;Serpero, Sabatini, Colivicchi, & Gazzolo, 2013).…”
Section: Discussionmentioning
confidence: 99%